Development and Sea Trial of the Terrain Monitoring Device Based on MEMS Sensing Array. Issue 7 (October 2021) - Ge, Y Q; Chen, J W; Cao, C; He, J M; Zhou, P; Gao, F; Xu, C Y
Abstract: Seabed terrain monitoring is an important and essential part of the environmental monitoring and early warning system in the process of trial production of natural gas hydrate. Since the first exploitation of natural gas hydrates in the South China Sea in 2017, China has once again succeeded in trial production of combustible ice in the sea area using horizontal well drilling technology in March 2020, which has achieved another major achievement in the process of industrialization. Therefore, for the purposes of ensuring green and safe development of natural gas hydrate, it is necessary to carry out research on the monitoring technology and equipment of seabed topography changes. This paper proposed a submarine terrain monitoring system based on MEMS (Micro-Electro-Mechanical System) sensor array. In November 2020, the developed device was successfully deployed in the Shenhu area of the South China Sea to perform in-situ monitoring mission for 6 months. Sea trial results proved that the terrain monitoring device can successfully monitor the subsidence and uplift of the seabed and provide a guarantee for the safe exploitation of natural gas hydrates.